2010
DOI: 10.1002/jts.20589
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of exposure therapy for Japanese patients with posttraumatic stress disorder due to mixed traumatic events: A randomized controlled study

Abstract: The authors examined the efficacy of Prolonged Exposure (PE) therapy in Japanese patients with posttraumatic stress disorder (PTSD). Twenty-four patients (21 women, 3 men) with PTSD due to mixed trauma were randomly assigned to the PE group (PE with or without treatment as usual [TAU]) or the control group (TAU) only. The control group received PE after a 10-week period. Intention-to-treat analysis showed the PE group achieved significantly greater reduction than the control group at posttreatment in either PT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 29 publications
1
58
1
1
Order By: Relevance
“…This finding is striking given that the study compared the efficacy of the treatment development team to community-based therapists who had minimal prior experience in delivering manual-based CBT interventions. Community-based therapists have produced similar results in their delivery of PE for PTSD in Japan (Asukai et al, 2010) and Israel (Nacasch et al, 2010) and achieved outcomes far superior to treatment as usual. These examples and others are discussed in greater detail below in the section on “Meeting the Global Need” and demonstrate that PE is readily adaptable to community settings with non-expert clinicians.…”
Section: Current Use Of Ebts For Ptsd By Mental Health Cliniciansmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding is striking given that the study compared the efficacy of the treatment development team to community-based therapists who had minimal prior experience in delivering manual-based CBT interventions. Community-based therapists have produced similar results in their delivery of PE for PTSD in Japan (Asukai et al, 2010) and Israel (Nacasch et al, 2010) and achieved outcomes far superior to treatment as usual. These examples and others are discussed in greater detail below in the section on “Meeting the Global Need” and demonstrate that PE is readily adaptable to community settings with non-expert clinicians.…”
Section: Current Use Of Ebts For Ptsd By Mental Health Cliniciansmentioning
confidence: 99%
“…PE produces significantly greater pre- to posttreatment reductions in PTSD symptoms compared to supportive counseling (Bryant, Moulds, Guthrie, Dang, et al, 2003; Schnurr et al, 2007), relaxation training (Marks, Lovell, Noshirvani, Livanou, & Thrasher, 1998; Taylor et al, 2003; Vaughan, Armstrong, Gold, & O'Connor, 1994), and “treatment as usual” including pharmacotherapy (Asukai, Saito, Tsuruta, Kishimoto, & Nishikawa, 2010), non-exposure-based individual psychotherapy (Boudewyns et al, 1990), and combinations of psychopharmacology, counseling, and group therapy (e.g., Nacasch et al, 2010). A similar protocol developed by Marks et al (1998) employs imaginal and in vivo exposure sequentially, instead of concurrently.…”
Section: Exposure Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…and assigning in vivo exposures for homework . This protocol has been found successful with a diverse range of patient populations in a range of clinical settings (Powers, Halpern, Ferenschak, Gillihan, & Foa, 2010), e.g., community clinic and academic research clinics (Foa et al, 2005;Ironson, Freud, Strauss, & Williams, 2002); HIV-positive patients (Pacella et al, 2012); rape survivors (Foa, Rothbaum, Riggs, & Murdock, 1991;Resick et al, 2002;Rothbaum, Astin, & Marsteller, 2005); male and female veterans (Thorp, Stein, Jeste, Patterson, & Wetherell, 2012;Schnurr et al, 2007), and Japanese men and women (Asukai, Saito, Tsuruta, Kishimoto, & Nishikawa, 2010).…”
Section: Cognitive-behavioral Approachesmentioning
confidence: 99%
“…They are directly related to the fear and anxiety that they generate to those who suffer. For the treatment of these disorders, we have demonstrated that exposure-based on therapies are more appropriate and effective than other ones [3][4][5][6][7][8][9][10][11]. Allowing patients to overcome their phobias in a progressive way.…”
Section: Introductionmentioning
confidence: 99%